Nimotuzumab Induces NK Cell Activation, Cytotoxicity, Dendritic Cell Maturation and Expansion of EGFR-Specific T Cells in Head and Neck Cancer Patients - Mazorra, Zaima; Lavastida, Anabel; Concha-Benavente, Fernando; Valdés, Anet; Srivastava, Raghvendra M.; García-Bates, Tatiana M.; Hechavarría, Esperanza; González, Zuyen; González, Amnely; Lugiollo, Martha; Cuevas, Iván; Frómeta, Carlos; et al. (Frontiers in Pharmacology, 2017)
Survival benefit and long-term duration of clinical response have been seen using the epidermal growth factor receptor (EGFR)-targeted monoclonal antibody (mAb) nimotuzumab. Blocking EGFR signaling may not be the only mechanism of action underlying its efficacy. As an IgG1 isotype mAb, nimotuzumab’s capacity of killing tumor cells by antibody dependent cellular cytotoxicity (ADCC) and to induce an immune response in cancer patients have not been studied. ADCC induced by nimotuzumab was determined using a 51Cr release assay. The in vitro effect of nimotuzumab on natural killer (NK) cell activation and dendritic cell (DC) maturation and the in vivo frequency of circulating regulatory T cells (Tregs) and NK cells were assessed by flow cytometry. Cytokine levels in supernatants were determined by ELISA. ELISpot was carried out to quantify EGFR–specific T cells in nimotuzumab-treated head and neck cancer (HNSCC) patients. Nimotuzumab was able to kill EGFR+ tumor cells by NK cell-mediated ADCC. Nimotuzumab-activated NK cells promoted DC maturation and EGFR specific CD8+ T cell priming. Interestingly, nimotuzumab led to upregulation of some immune checkpoint molecules on NK cells (TIM-3) and DC (PD-L1), to a lower extent than another EGFR mAb, cetuximab. Furthermore, circulating EGFR-specific T cells were identified in nimotuzumab-treated HNSCC patients. Notably, nimotuzumab combined with cisplatin-based chemotherapy and radiation increased the frequency of peripheral CD4+CD39+FOXP3+ Tregs which otherwise were decreased to baseline values when nimotuzumab was used as monotherapy. The frequency of circulating NK cells remained constant during treatment. Nimotuzumab-induced, NK cell-mediated DC priming led to induction of anti-EGFR specific T cells in HNSCC patients. The association between EGFR-specific T cells and patient clinical benefit with nimotuzumab treatment should be investigated.